(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2004)
This paper deals with the geological context of the northernmost site in the East Africa Rift system which has yielded Homo erectus-like remains. They are dated ca. 1 Ma and have been found in the deltaic deposits of the Alat Formation belonging to the Dandiero group. This newly defined group crops out extensively in an elongated belt from the Gulf of Zula to the North to the Garsat area to the south. In the Buia-Dandiero area it ranges in age from the Early to the Middle Pleistocene, and incorporates six formations, from bottom up: the fluvial Bukra Sand and Gravel, the deltaic and lacustrine Alat Formation, fluvial Wara Sand and Gravel, the lacustrine Goreya Formation, the fluvio-deltaic Aro Sand and alluvial Addai Fanglomerate. This succession is bounded by two major unconformities, which separate it from the Neoproterozoic basement and from the overlaying Boulder Beds fanglomerate, and has been designated the Maebele Synthem. The latter is the result of two lacustrine transgression and regressions evidenced by two depositional sequences. The unconformities bounding the Maebele Synthem are related to the tectonic history of the basin fill and its substrate. The development of the two sequences was, instead, mainly controlled by lake level fluctuations and, hence, by climatic variations connected with the weakening and strengthening of the monsoons in the northwestern Indian ocean. The environment where the Buia Homo lived was a savannah with some scattered water pools. This environment probably extended farther north along the western coastal plain of the Red Sea, and was a preferential pathway for the dispersal of the hominids from East Africa toward Eurasia.